Geometry Versus Drawing: Changing the Meaning of the Task as a Means to Change Performance - Huguet, Pascal; Brunot, Sophie; Monteil, Jean Marc (Social Psychology of Education, 2001)
There is now much convincing evidence that the context in which children are given cognitive tasks can have a huge effect on their performance in those tasks, even when the experimental and control conditions make exactly the same logical and cognitive demands. According to this, we found that children faced with a cognitive-perceptual task (the Rey–Osterrieth's complex figure reproduction test) performed better or worse in one context (geometry) than in another (drawing), depending on their performance history in these contexts, although the task was the same in both conditions. These effects are discussed both in relation to underlying processes and in perspective with another phenomenon (stereotype threat) which also provides evidence for the social regulation of cognitive functioning in the school environment.
Keywords: Academic Achievement; Educational Context; Stereotype Threat; Stroop Task; Test Anxiety